ANALYSIS OF RISK FACTORS FOR THE INCIDENT OF PNEUMONIA IN TODDLER CHILDREN AGED 12-59 MONTHS IN THE AREA OF THE KALIBARU HELPING PUSKESMAS NORTH JAKARTA - Deranita, Sri; Sahrudi, Sahrudi (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Background: Pneumonia in toddlers is one of the main causes of death in Indonesia. Around 150,000 children under five are estimated to die every year from pneumonia. The majority of deaths occur in infants. Worldwide, it is estimated that more than 2 million toddlers die from pneumonia every year, which means one toddler dies every 20 seconds. Objective: to study the analysis of risk factors for the incidence of pneumonia in children under five aged 12-59 months in the Kalibaru Sub- Puskesmas Area, North Jakarta. Method: cross-sectional population is all children who experienced pneumonia at the Kalibaru Sub-Public Health Center, North Jakarta. The population in this study was 112 people. The sample in this study was 90 people, with a sampling technique using simple random sampling, analysis using univariate and bivariate. Results: From the results of statistical tests on the incidence of pneumonia, the majority of respondents, 53 (58.9%) of respondents experienced pneumonia and almost 37 (41.1%) of respondents did not experience pneumonia. There is a relationship (age of toddler p-value 0.028 OR value =3.560, gender p-value 0.015 OR value =3.277, immunization status p-value 0.028 OR value =3.560, nutritional status p-value 0.016<α =0.05 OR value = 3,491 with the incidence of pneumonia. There is no relationship (education, maternal occupation, access to health services, and area of residence) with the incidence of pneumonia at the Kalibaru Cilincing sub-district health center, North Jakarta. Conclusion: It is hoped that health workers can provide additional information regarding the factors that cause pneumonia so that they can provide preventative solutions when providing education, especially at POLI MTBS and MTBM.